Risk Factors for Abdominal Wound Dehiscence in Surgical Department Lady Reading Hospital Peshawar - Naz, Shakeela; Gul, Ayaz (Indus Journal of Bioscience Research, 2025)
Background: Abdominal wound dehiscence, is a severe surgical complication that can result in prolonged hospitalization, higher rates of morbidity, and even death. The purpose of this study was to identify the risk variables for AWD in patients having abdominal operations at Lady Reading Hospital in Peshawar. Methods: A descriptive cross-sectional study was conducted over six months involving 141 patients aged 25–70 years undergoing abdominal surgery. A standardized proforma was used to gather data on steroid use, diabetes, obesity, and anemia. IBM SPSS version 22 was used for the statistical analysis, and chi-square tests were used to evaluate associations (p-value < 0.05 was deemed significant). Results: Twenty-eight patients (26.2%) experienced AWD. The risk factors that were most common were steroid use (12.8%), diabetes (23.4%), obesity (17.0%), and anemia (29.1%). AWD and steroid use (p=0.009), diabetes (p=0.018), obesity (p=0.022), and anemia (p=0.008) were found to be statistically significantly associated. There was a higher frequency of AWD in males and older adults, but these differences were not statistically significant. Conclusion: Significant risk factors for AWD include anemia, diabetes, obesity, and steroid usage. Finding and improving these modifiable characteristics can lower the incidence of AWD, enhance surgical results, and ease the strain on healthcare systems. It is strongly advised to incorporate preventive measures into perioperative treatment, particularly for patients who are at high risk.